Potensi Pemanfaatan Ekstrak Kubis Ungu (Brassica oleracea L.) sebagai Indikator Asam Basa Alami - Erwin -; Muhammad Asfian Nur; Aman Sentosa Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
The study of potential use of extracts and fractions of purple cabbage (Brassica oleracea L.) as an indicator of acid-base has been conducted. This research aims to determine the color change at a certain pH to extract total, n-hexane, ethyl acetate and methanol fraction. Based on the results of the test changes color only total extracts and methanol fraction that is suitable as indicator. Statistical test that the t test for total titration end point extracts, t calculate is smaller than t table [0.4241 <2.776], it showed no significant difference between the endpoint using the total extract with bromine thymol blue indicator. While the endpoint for methanol fraction having t calculategreater than t table [6.323> 2.776],indicating the end point of the titration using methanol fraction was significantly different compared with bromine thymol blue indicator.Keywords: Brassica oleracea L, indicator, and acid-base